p38 Mitogen-Activated Protein Kinase Contributes to Angiotensin II-Stimulated Migration of Rat Aortic Smooth Muscle Cells - Hwan Myung Lee; Chang-Kwon Lee; So Hee Lee; Hui Yul Roh; Young Min Bae; Kyung-Yung Lee; Jaegeun Lim; Pyo-Jam Park; Tae-Kyu Park; Yun Lyul Lee; Kyung-Jong Won; Bokyung Kim (Elsevier, 2007)
In this study, we clarified the intracellular mechanism of angiotensin II (Ang II) in promoting migration in rat aortic smooth muscle cells (RASMCs). RASMC migration was measured with the Boyden chamber assay, and the result was confirmed with an aortic sprout assay. The activities of kinases were investigated by western blot analysis. Ang II enhanced RASMC migration, which was chemotaxis directed, and induced the phosphorylation of p38 mitogen-activated protein kinase (MAPK), extracellular signal-regulated kinase 1/2 (ERK1/2), and heat shock protein 27 (Hsp27). Ang II-enhanced cell migration was inhibited by SB203580 (a p38 MAPK inhibitor) and piceatannol (a spleen tyrosine kinase inhibitor), but only partially by PD98059 (an ERK inhibitor) and PP2 (a Src inhibitor). The Ang II-stimulated phosphorylation of p38 MAPK and Hsp27 in RASMCs was inhibited by piceatannol and SB203580. The phosphorylation of ERK1/2 stimulated by Ang II was suppressed by PD98059, piceatannol, and PP2. Ang II increased the sprout outgrowth from aortic rings and this response was attenuated by pretreatment with SB203580, PD98059, PP2, or piceatannol. These results suggest that p38 MAPK contributes to the regulation of the Ang II-induced chemotactic migration of vascular smooth muscle cells, which is mediated by Hsp27 phosphorylation. Keywords:: angiotensin II, migration, rat aortic smooth muscle cell (RASMC), p38 mitogen-activated protein kinase (MAPK), heat shock protein 27 (Hsp27)